Early Advanced Therapy for Diabetic Foot Ulcers in High Amputation Risk Veterans: A Cohort Study. (June 2022) - Doucette, Margaret; Payne, Kattie M.; Lough, Walter; Beck, Alison; Wayment, Kristi; Huffman, John; Bond, Laura; Thomas-Vogel, Aurora; Langley, Susan
Veterans with diabetic foot ulcers (DFUs) represent the highest percentage of lower extremity amputations (LEAs) within the Veterans Affairs (VA) population. Many veterans have additional risk factors for amputation. Few studies focus on advanced therapies for this population. This study explores the impact of early application of dehydrated human amniotic membrane allograft (DAMA) with comprehensive care on preventing amputation. This prospective, single-center cohort study (ClinicalTrials.gov Identifier NCT02632929) was conducted through Boise VA Medical Center. Patients with DFUs were objectively stratified for LEA risk. Those with moderate to high amputation risk could participate. Participants received comprehensive care and weekly application of DAMA. Primary endpoint was avoidance of major LEA. Secondary endpoint was wound epithelialization. Monitoring continued 4 months. Between July 2015 and March 2017, 20 patients (mean age 67.2 years) with 24 DFU classified as moderate (12 wounds) to high risk (12 wounds) for amputation were enrolled. Wound volumes ranged from 0.072 cm 3 to 56.4 cm 3 . Risk factors included neuropathy (20 patients), osteomyelitis (16 wounds), exposed tendon/ligament/bone (19 wounds), Charcot (5 patients), and peripheral arterial disease (13 wounds). All subjects avoided amputation within the study period, all 24 wounds achieved re-epithelialization within 4 to 33 weeks; mean healing time 13.2 weeks. Cost for the DAMA tissue ranged from $750 to $38 150. Estimated cost for LEA ranges from $30 000 to $50 000. No treatment-related adverse events during the study period were reported. The results suggest that early and frequent application of DAMA with comprehensive care may help prevent amputation. Additional research will help inform third-party payors and clinicians.